Educating Science Teachers for Sustainability
XXI, 478 p. 48 illus., 39 illus. in color.
Keywords: This volume contains a unique compilation of research and reflections representing multiple vantage points stemming from different parts of the world that can help science educators and teacher educators in finding ways to meaningfully and purposefully embed sustainability into teaching and learning. It is a rich resource for exploring and contextualizing sustainability-oriented science education. At this time we find ourselves in a situation in which the earth’s ecological system is under significant strain as a result of human activity. In the developed world people are asking “How can we maintain our current standard of living?” while those in the developing world are asking “How can we increase the quality of our lives?” all while trying to do what is necessary to mitigate the environmental problems. This volume responds to these questions with a focus on educating for sustainability, including historical and philosophical analyses, and pedagogical and practical applications in the context of science teacher preparation. Included are many examples of ways to educate science teachers for sustainability from authors across the globe. This text argues that issues of sustainability are increasingly important to our natural world, built world, national and international economics, and of course the political world. The ideas presented in the book provide examples for original, effective and necessary changes for envisioning educating science teachers for sustainability that will inform policy makers.